Colonial Encounters Towards Agrarian Change: A Study of the Agricultural Landscape in Bukidnon During the American Period, 1901-1935 (British Journal of Multidisciplinary and Advanced Studies, 2025)
This paper seeks to present how the interaction between the native populations and American colonizer drastically altered the agricultural landscape of Bukidnon. As integrated into the colonial agricultural system, Bukidnon evolved into a modern economy. The American colonists brought a new set of agricultural policies, which led to the establishment of agricultural colonies, major plantations and new crop productions, which profoundly changed Bukidnon's agrarian structure. The agricultural development of Bukidnon during the American colonial era is the main subject of the study. It highlights the cooperation between the native people and the American colonists, asserting that traditional farming and colonial imposition shaped Bukidnon's agricultural landscape. The researcher has effectively consolidated primary sources and utilized secondary materials to conduct a thorough analysis of the study. By employing qualitative data generated through archival research and a historical-narrative approach, this study presents the relationship between Americans and natives within the agricultural landscape of Bukidnon. This research answers the following questions: What was Bukidnon's agricultural landscape prior to American colonization? What key agricultural policies did the Americans implement? How did the colonial interactions with the natives shape Bukidnon's agricultural landscape? Therefore, this study deals with Bukidnon's agricultural development in the period of American colonial rule. It stresses the role of collaboration in the interactions of natives and American colonizers, arguing that the agricultural landscape of Bukidnon is the result of both colonial imposition and sedentary farming practices. The results of the study offered a deep perspective on the effects of the American period in Bukidnon, and their continued influence on agricultural problems and practices today.